Aerosols exposure and respiratory morbidity among dental health care Professionals of Lucknow - Mahmood, Syed Esam; Ahmad, Ausaf; Ahmad, Nadeem; Muzammil, Khursheed; Chander, Mahesh; Siddiqui, Shireen (Indian Journal of Community Health, 2019)
Introduction: Dentists use high-energy equipment, such as drills and scalers in the presence of bodily fluids such as blood and saliva, and dental plaque. This combined effect generates aerosols of oral micro-organisms, and blood. Objective: To determine the prevalence of respiratory morbidities and practices for protection against aerosols exposure at work place among dental health care professionals in District Lucknow. Methods: This cross-sectional study involved private dental practitioners registered with Indian Dental Association chosen by Simple Random Sampling. Dentists who gave consent and who were practicing for at least 1 year were included. Aerosol exposure and respiratory morbidity was assessed using a self-administered questionnaire. SPSS software version 16.0 was used for data analysis. Results: Total number of study participants were 0. Mean age in years of study subjects were 33.5 ±11.6. Their average years of involvement in clinical practice were 10.0 ±12.75. Majority of dental practitioners used hand scalers (70%) and power scalers (80%) on patients. A higher proportion changed their masks by the day (60%). Majority used protective eye goggles (70%). Only 30% used high efficiency particulate room filters while 20% used humidifiers and air purification systems. One fifth of respondents usually had cough. Conclusion: Respiratory morbidity is associated with workplace generated aerosol among dental health professionals. Awareness regarding occupational exposure and implementation of preventive strategies is required to provide a safe working environment.